Avaliação do efeito da inibição química das funções redox e reparo de APE1/Ref-1 sobre a transcrição gênica durante a inflamação - Oliveira, Thais Teixeira (2020)
APE1/Ref-1 is a protein that has two functional domains in mammals. The N-terminal domain is capable of reducing transcription factors, such as NF-kB, AP-1 and HIF-1 and increase its DNA binding capabilities and the expression of its target genes. The C-terminal domain, on the other hand, is responsible for the endonuclease activity of APE1/Ref-1, which is the main endonuclease of the base excision repair (BER) pathway that acts in the repair of apurine/apyrimidine (AP) sites. Due to this, APE1/Ref-1 is a potentially well-studied therapeutic target, especially in relation to cancer. Recently, it has been demonstrated that the presence of 8-oxoG, the main oxidized DNA damage, in the promoters of some genes can result in the induction of gene expression in the presence of DNA glycosylase OGG1 and APE1/Ref-1. Thus, APE1/Ref-1 also regulates gene expression in a manner dependent on its endonuclease function. However, the role of each of the APE1/Ref-1 functions on transcriptional regulation is not yet fully elucidated. In a previous work by our group, it was observed through RNAseq, that the inhibition of APE1/Ref-1 endonuclease activity by methoxyamine changes the expression of several genes during inflammation as well as decreases the expression of cytokines and chemokines in LPS-treated monocytes. Thus, the objective of this research was to verify which other genes have expression affected by the inhibition of AP repair, as well as to identify through bioinformatics tools possible regulators and partners of APE1/Ref-1 in this response. For this, RNA-seq was re-analyzed using bioinformatics tools and updated databases. In addition, the genes differentially expressed after treatment with methoxyamine were analyzed for their functions and possible regulators of their expression. The analysis of the transcriptome indicated that treatment with methoxyamine increases the expression of genes related to inhibition of the mTORC1 pathway and the protein polyubiquitination. On the other hand, it reduces the expression of genes related to cell cycle progression, transcription, expression of mitochondrial genes, biosynthesis of prostaglandins and Toll-like signaling independent of MyD88. In addition, these genes were compared with those differentially expressed after treatment with E3330 (specific inhibitor of redox function) under the same conditions. The main regulators of common genes as well as their targets were analyzed for their expression using q-PCR and Western blot. It was observed that both, the repair and redox function of APE1/Ref-1, are able to decrease the transcription of NRF1, GABPA and ELK1 target genes. These genes are related to mitochondrial biogenesis, rRNA processing and ribosomal biogenesis. In addition, it was observed that both APE1 / Ref-1 functions similarly decrease the expression of genes related to mitochondrial biogenesis, as well as being able to decrease Myc expression. On the other hand, the expression of ribosomal proteins was mainly affected by E3330, while inhibition of DNA repair was able to decrease the expression of the 47S pre-rRNA without affecting the processing of this RNA. Finally, we can conclude that both functions of APE1/Ref-1 may be involved in the regulation of genes related to mitochondrial biogenesis, but play different roles in the regulation of genes related to the processing and transcription of rRNA.